FUNDAMENTALS OF THE FORMATION AND FUNCTIONING OF MARKETING ACTIVITIES OF HIGHER EDUCATIONAL INSTITUTIONS (Scientific electronic journal "Labor Economics and Human Capital", 2024)
In today's globalized world, where education plays a significant role in all aspects of life, the international appeal of higher education institutions has become a crucial factor in their success. This makes the study of marketing practices in these institutions an urgent and important task. A scientific article on the topic can provide a comprehensive analysis of current approaches and techniques used in marketing educational services, identify their effectiveness, and suggest ways to improve and develop marketing strategies for educational institutions in today's rapidly changing educational and social environment.
Keywords: marketing, strategies, higher education, innovations in the marketing of educational services, branding of educational institutions.